The effects of innovation and digitalization on business dynamism: an empirical study from Italian regions - Alessandra Patti; Valeria Schifilliti (Journal of Economics and Business Letters, 2023)
The fast pace of innovation and digitalisation has recently changed economic equilibria that need attention from scholars and policymakers. To this end, this paper empirically investigates the relationship between innovation and digitalisation on the churn rate of Italian businesses in industries, constructions, and services from 2010 to 2019. The main findings suggest that, on average, innovation and current and past territorial development of Information and Communication Technologies (ICTs) positively influence the churn rate of businesses in all Italian regions. However, the effects of innovation are remarkable on the business churn rate of northern regions only, evidencing the existence of a "business dynamism divide" between the North and South of Italy.